STUDIES ON Aeromonas hydrophila BACTERIA DISEASES IN WILD AND CULTURED ELVER EEL (Anguilla bicolor) - Noviana Dewi; Isti Koesharyani (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
This study was performed to detect Aeromonas hydrophila infection in wild and cultured elver eel (Anguilla bicolor). In total, 20 live elvers (10 wild and 10 cultured) were collected and subjected to Aeromonas hydrophila tests. Polymerase chain reaction (PCR) was done for an accurate identification of Aeromonas hydrophila using a universal primer and detection of the aerolysin gene in A. hydrophila using a specific primer. The virulence of A. hydrophila was determined using a pathogenicity test injection. The results showed that A. hydrophila could be detected using PCR and amplification of 685bp DNA. A. hydrophila could also be confirmed to contain the aerolysin gene of 290 bp DNA which could be a virulence indicator. Pathogenicity test revealed that LC50 was estimated to be 10.9 x 10 6.33. Histopathological changes were found in the abdominal and wounded muscles. Those changes were mainly in tissue ephitel cell hyperplasia. Based on the present study, A. hydrophila is a virulent bacteria in elver eel. A. hydrophila disease preventive measures need to be formulated. Elver eels should be tested for the A. hydrophila before restocking into farms.